Aurora Cafe / Nurul Fadzeera Aleeda Aldana... [et al.] - Aldana, Nurul Fadzeera Aleeda; Hamdin, Hasimah; Basir, Nurul Aida Shafizah; Suratno, Mohd Fandi; Daripin, Joejie (2014)
The name of our cafe is Aurora. It is a partnership business consists of five contributors. We are targeting to expand our business throughout the world in long term achievement. At first, we realize that the demand for cafe services especially coffee has increased in Sabah. However, most of the cafe that already exist seems to offer the same types of product. Thus, we take the initiative to bring a new variety of coffee solely themed as an Italian and a variety of most popular cupcakes worldwide. We have confident that if we manage to put the new themed menu for our cafe plus the variety of most popular cupcakes, we could be a stand out as we are the first to do so in the area of Kota Kinabalu. The idea then becomes action when five of us agreed to become partner and become entrepreneur in this business. Hence, we believe that as a pioneer of a new and the first Italian themed menu cafe in Suria Sabah, we will able to strike the market.